2002
DOI: 10.1046/j.1439-0450.2002.00565.x
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Acid Fast Bacteria From Caseous Lesions in Cattle in Sudan

Abstract: One-hundred-and-twenty caseous lesions collected from slaughtered cattle at selected slaughterhouses in Sudan were processed for the detection of acid-fast bacteria (AFB). Sixty-four of the 120 samples showed AFB on microscopic examination after staining with the Ziehl-Neelsen method. Accordingly, it was estimated that 64 (53.3%) of the 120 caseous (purulent) lesions among the samples were due to AFB whereas 56 (46.7%) were due to other causes. Growth on Lowenstein-Jensen slants was obtained in 54 of the 120 s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
1
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 20 publications
3
20
1
2
Order By: Relevance
“…Sulieman and Hamid (22) found that 64 (53.3%) of 120 caseous lesions from cattle in Eastern and Central Sudan were due to acid-fast bacilli (AFB), whereas 56 (46.7%) were due to other causes. Growth on Lowenstein-Jensen slants was obtained in 52 of the 120 samples and identified as follows: 25 (48.1%) Mycobacterium bovis, 21 (40.4%) M. farcinogenes, 4 (7.7%) M. tuberculosis, 1 (1.…”
mentioning
confidence: 99%
“…Sulieman and Hamid (22) found that 64 (53.3%) of 120 caseous lesions from cattle in Eastern and Central Sudan were due to acid-fast bacilli (AFB), whereas 56 (46.7%) were due to other causes. Growth on Lowenstein-Jensen slants was obtained in 52 of the 120 samples and identified as follows: 25 (48.1%) Mycobacterium bovis, 21 (40.4%) M. farcinogenes, 4 (7.7%) M. tuberculosis, 1 (1.…”
mentioning
confidence: 99%
“…Animal reproduction and breeding as well as livestock trade at national and international levels are directly and adversely affected by mycobacterial infections (Radostits et al, 2007;Ehsan and Nganwa, 2014;Ramos et al, 2015). TB and other mycobacterial infections are quite prevalent in dairy growing mycobacterium species have also been detected (Sulieman and Hamid, 2002;Oloya et al, 2007;Osman, 2007;Manal et al, 2010;Asil et al, 2013;Aljameel et al, 2014;Nalapa et al, 2017). Environmental risk factors, malnutrition, presence of other diseases, and heavy infestation with endoparasites are important factors that increase the susceptibility of animals to TB (Radostits et al, 2007;Ehsan and Nganwa, 2014).…”
Section: ■ Resultsmentioning
confidence: 99%
“…A detecção de bacilos álcool-ácido resistentes (BAAR) em somente três búfalos demonstra a baixa sensibilidade da técnica, uma vez que 13 animais apresentaram resultados positivos nas técnicas de Nested-PCR. A baixa sensibilidade da coloração de Ziehl-Neelsen é relatada em bubalinos (Garine-Wichatitsky et al 2010, Laisse et al 2011) e em bovinos (Cancela & Marín 1993, Sulieman & Hamid 2002, Watrelot-Virieux et al 2006. Um animal que apresentava BAAR foi negativo aos testes moleculares.…”
Section: Discussionunclassified
“…(Muller et al 2011), Nocardia sp. (Sulieman & Hamid 2002), Streptococcus spp., ou serem decorrentes de micobacterioses atípicas, capazes de interferir em sistemas de PCR pouco sensíveis (Sahraoui et al 2009, Thacker et al 2011. Outra possibilidade seria a falha de sensibilidade das técnicas de Nested-PCR, uma vez que o diagnóstico diretamente em tecidos tem apresentado sensibilidade clínica média de até 75% (Araújo et al 2014a, Araújo et al 2014b.…”
Section: Discussionunclassified